2017
DOI: 10.1093/humupd/dmx008
|View full text |Cite
|
Sign up to set email alerts
|

Sperm recovery and ICSI outcomes in Klinefelter syndrome: a systematic review and meta-analysis

Abstract: The present data suggest that performing TESE/micro-TESE in subjects with KS results in SRRs of close to 50%, and then PRs and LBRs of close to 50%, with the results being independent of any clinical or biochemical parameters tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
3
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 65 publications
10
171
3
5
Order By: Relevance
“…These patients with spermatozoa with maturation arrest had a higher frequency of genetic anomalies, compared to NOA patients . Male age also is considered to be a predictive factor in KS cases . The hormonal level indication is not intended to set the criteria for the positive or negative result of sperm retrieval; it is important to comprehend the patient's background by receiving adequate patient information prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These patients with spermatozoa with maturation arrest had a higher frequency of genetic anomalies, compared to NOA patients . Male age also is considered to be a predictive factor in KS cases . The hormonal level indication is not intended to set the criteria for the positive or negative result of sperm retrieval; it is important to comprehend the patient's background by receiving adequate patient information prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported by Majzoub et al indicated that publications from many different centers documented sperm retrieval rates (SRRs) in KS adults of approximately 50%‐70%, which are higher than those of general NOA cases, and reported excellent pregnancy rates and healthy 46,XY or 46,XX offspring. A recent meta‐analysis has shown an overall SRR of approximately 40%, ranging from 1% to 50%, in both conventional TESE and micro‐TESE . These results indicate that micro‐TESE, but not conventional TESE, is an ideal method to retrieve sperm from men with KS.…”
Section: Ks and Infertility Treatmentmentioning
confidence: 95%
“…Taking these results together with the biological information that progressive hyalinization of seminiferous tubules is observed after puberty in men with KS, it has been suggested that performing earlier TESE procedures might result in better SRR results . A meta‐analysis has shown that successful SRR in KS patients is independent of age …”
Section: Is Tese During Adolescence Effective In Ks Patients?mentioning
confidence: 99%
“…This group includes patients with Klinefelter syndrome (KS) and Turner syndrome (TS). Males with KS most commonly have a 47,XXY karyotype and impaired spermatogenesis (50). Historically these patients were all thought to be sterile.…”
Section: Impaired Fertility Related To Underlying Medical Conditionsmentioning
confidence: 99%
“…Historically these patients were all thought to be sterile. However, it has been found that some men with KS have a small number of cells that retain the ability to undergo spermatogenesis, and micro-TESE results in sperm retrieval in 50% of men with KS (50,51). With small studies showing no clear benefit of pursuing retrieval in adolescence, the current recommendation is to obtain an ejaculated sample as soon as possible after puberty begins (with cryopreservation of any viable sperm) and to offer micro-TESE at 15-30 years of age (52)(53)(54).…”
Section: Impaired Fertility Related To Underlying Medical Conditionsmentioning
confidence: 99%